Synthesis, Photophysics and Nonlinear Optical Properties of Stilbenoid Pyrimidine‐Based Dyes Bearing Methylenepyran Donor Groups. Issue 12 (2nd July 2013) - Achelle, Sylvain; Malval, Jean‐Pierre; Aloïse, Stéphane; Barsella, Alberto; Spangenberg, Arnaud; Mager, Loic; Akdas‐Kilig, Huriye; Fillaut, Jean‐Luc; Caro, Bertrand; Robin‐le Guen, Françoise
Abstract The nonlinear properties and the photophysical behavior of two π‐conjugated chromophores that incorporate an electron‐deficient pyrimidine core (A) and γ‐methylenepyrans as terminal donor (D) groups have been thoroughly investigated. Both dipolar and quadrupolar branching strategies are explored and rationalized on the basis of the Frenkel exciton model. Even though a cooperative effect is clearly observed if the dimensionality is increased, the nonlinear optical (NLO) response of this series is moderate if one considers the nature of the D/A couple and the size of the chromophores (as measured by the number of π electrons). This effect was attributed to a disruption in the electronic conjugation within the dyes' scaffold for which the geometry deviates from planarity owing to a noticeable twisting of the pyranylidene end‐groups. This latter structural parameter also has a strong influence on the excited‐state dynamics, which leads to a very efficient fluorescence quenching.